Do Brand Personality and Celebrity Endorser Influence Customer Loyalty through Brand Trust? (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
In an attempt to maintain customer loyalty to Madame Gie Cosmetic, it is necessary to innovate in promotion and marketing. Factors that can affect customer loyalty are brand personality and celebrity endorsers which are also related to brand trust variables. So, the purpose of this study is to examine the effect of brand personality and celebrity endorsers on customer loyalty through brand trust on Instagram followers of the Madame Gie Cosmetic brand.  The approach used is quantitative research with descriptive explanatory and questionnaire filling methods. Research data obtained from 320 respondents. Data processing is done using Smart-PLS software.  Data were analyzed by descriptive analysis, outer model, inner model and hypothesis testing with t-statistic value for alpha 5%. The results of this study are Brand personality has a positive and significant effect on customer loyalty and brand trust.  Celebrity endorsers have a positive and insignificant effect on customer loyalty and brand trust. Brand trust has a positive and significant effect on customer loyalty. Brand personality and Celebrity endorsers have a positive and significant effect on customer loyalty through brand trust. While the general relationship between brand personality, celebrity endorsers, and customer loyalty has been explored in previous studies, the specific findings of this research contribute to the existing knowledge in several ways: Mediating role of brand trust and Specificity to Madame Gie cosmetics. The contribution of these findings may help theoretical advancement, practical implications, and specific insights for Madame Gie cosmetics. In summary, the novelty of the study lies in its identification of brand trust as a mediator, while its contributions include theoretical advancement, practical implications, and specific insights for the brand.